ФОЛьКЛОР И РУССКАЯ ЛИТЕРАТУРА XI−XVIII ВВ. В ИССЛЕДОВАНИЯХ ПОЛЬСКИХ УЧЕНЫХ 1990−2015 ГОДОВ - Małek, Eliza (Przegląd Rusycystyczny, 2016)
FOLKLOR I LITERATURA ROSYJSKA XI–XVIII W. W BADANIACH POLSKICH UCZONYCH Z LAT 1990–2015 W artykule został scharakteryzowany wkład polskich uczonych do badań nad rosyjskim folklorem, literaturą XI–XVIII w. oraz częściowo polsko-rosyjskich związków literackich tego okresu. FOLKLORE AND RUSSIAN LITERATURE OF XI-XVIII CENTURIES THROUGH THE EYES OF POLISH SCHOLARS 1990–2015 This paper describes the contribution of Polish scholars to the study of Russian folklore, Russian literature of 11–18th Centuries and Polish-Russian literary contacts.